Unveiling the Public Economic Burden of Migraine in Argentina - Zrinka Orlović; Lucila Rey-Ares; María Florencia Viozzi; Rui Martins; Juliana Villarreal Ramírez; Santiago Veiga; Mark P. Connolly (Journal of Health Economics and Outcomes Research, 2025)
# Background Migraine is a prevalent, underdiagnosed, highly debilitating neurological condition that affects individuals’ quality of life and often negatively influences normal daily activities.